2010
DOI: 10.1021/ac101337n
|View full text |Cite
|
Sign up to set email alerts
|

Microchip Electrophoresis Profiling of Aβ Peptides in the Cerebrospinal Fluid of Patients with Alzheimer’s Disease

Abstract: The preferential aggregation of Aβ1-42 in amyloid plaques is one of the major neuropathological events in Alzheimer's disease. This is accompanied by a relative reduction of the concentration of Aβ1-42 in the cerebrospinal fluid (CSF) of patients developing the signs of Alzheimer's disease. Here, we describe a microchip gel electrophoresis method in polydimethylsiloxane (PDMS) chip that enables rapid profiling of major Aβ peptides in cerebrospinal fluid. To control the electroosmotic flow (EOF) in the PDMS cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…28 The electrophoresis chip has channel cross section dimensions of 100 lm  50 lm  35 mm. The channel surface was coated by introducing a 0.2% solution of a homemade copolymer PDMA-AGE in ddH 2 O.…”
Section: Microchip Electrophoresis (Mce)mentioning
confidence: 99%
See 2 more Smart Citations
“…28 The electrophoresis chip has channel cross section dimensions of 100 lm  50 lm  35 mm. The channel surface was coated by introducing a 0.2% solution of a homemade copolymer PDMA-AGE in ddH 2 O.…”
Section: Microchip Electrophoresis (Mce)mentioning
confidence: 99%
“…28 Here, the MCE method was used for monitoring the lIP process by comparing the ratio of Ab isoforms in the sample before the lIP and in the elution fraction using two types of immunosorbents: one coated with mAb and one with pAb anti-Ab IgG (Fig. 8(a)).…”
Section: Mce For Comparing Magnetic Anti-ab Is (Mab and Pab)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, detection of these peptides in blood and urine is more difficult because their concentrations are 10-100 times smaller than in CSF (1 to 10 ng/mL). Mohamadi et al [53] described a two-step microchip analysis of five different β-amyloid peptides from CSF in PDMS devices. To enrich the target analytes, they performed immunocapture in a microchip and labeled the eluted analytes with fluorescent dye.…”
Section: Microchip Electrophoresis Analysismentioning
confidence: 99%
“…34 Although electrophoresis in microfluidic chips has been used to study the amyloid beta protein, thus far it has not been used to study its aggregation. 35 Additionally, while these studies have indicated the value and potential for using capillary or microchip electrophoresis to improve our understanding of FIG. 1.…”
Section: Introductionmentioning
confidence: 99%